Changes in Testes, Sperm Morphology and Peripheral Levels of FSH and LH in an Adult New Zealand Male Rabbit Exposed to Darkness - Akdader, Samira; Lakabi, lynda; Kamel, Assia; Hamouli-Said, Zohra (Polish Journal of Natural Sciences, 2025)
Biological rhythms control many physiological and behavioral functions in mammals, including reproduction. During the development of the reproductive system, testicular growth is primarily influenced by photoperiod, which is influenced by the circadian release of melatonin. The purpose of this study was to determine the effect of darkness on the gonadotropic axis in mature male rabbits. This study used ten male rabbits separated into two groups : a control group and a group that was placed in complete darkness for 15 days. After the sacrifice, using the IRMA method, blood samples were collected to assess serum LH and FSH hormone levels. Histopathology (testis) parameters were investigated and sperm smears were also obtained in order to investigate the morphological structure of the sperm collected. The results revealed morphological alterations in treated rabbits as well as a significant decrease in blood FSH and LH levels when compared to controls, suggesting a relationship between the gonadotropic axis and the pineal gland. The results of this study reveal that factors that activate the gonadotropic axis, such as darkness, can cause alterations in reproductive function, and that this is also dependent on photoperiod duration.